Homo itinerans towards a global ethnography of Afghanistan - Monsutti, Alessandro ca. 20.-21. Jh (Berghahn, 2021)
Afghan society has been marked in a lasting way by war and the exodus of part of its population. While many have emigrated to countries across the world, they have been matched by the flow of experts who arrive in Afghanistan after having been in other war-torn countries such as the Democratic Republic of the Congo, Palestine or East Timor. This book builds on more than two decades of ethnographic travels in some twenty countries, bringing the readers from Afghanistan, Pakistan and Iran to Europe, North America and Australia. It describes the everyday life and transnational circulations of Afghan refugees and expatriates
Description based on online resource; title from PDF title page (publisher's Web site, viewed 04. Okt 2022)
Keywords: Entwicklungshilfe; Gesellschaft; Konflikt; Wiederaufbau; Auswirkung; Entwicklung; SOCIAL SCIENCE / Anthropology / Cultural & Social; Afghans -- Foreign countries; Afghans; Refugees -- Afghanistan; Afghanen; Auswanderung; Mobilität; Afghanistan